The effect of endorsement and congruence on banner ads on sports websites - Lee, Woo-Young; Hur, Youngjin; Kim, Dae Yeon; Brigham, Christopher (International journal of sports marketing & sponsorship, 2017)
Purpose The purpose of this paper is to examine the effects of congruity and endorsement on consumer attitudes toward sports website advertisements (Aad), the advertising brand (Abr), and consumers’ future intentions (FI). Design/methodology/approach The current study followed a 2×3 between-subjects experimental design. Sports celebrity (or the presence or absence of a sports celebrity in a banner ad) and the level of congruity between the website and banner ad (high congruity – soccer, medium congruity – snowboard, and low congruity – computer) were the primary independent variables. Data were collected in two stages. An initial pilot study (n=40) established the reliability and validity of the scaled measures guiding this test. The second phase of data collection, the main study, was conducted over a five-day period. A random assignment of treatment conditions (i.e. exposure to one of six banner ad manipulations) was followed by a series of short surveys designed to measure the dependent variables of subjects’ cognitive ad responses (i.e. Aad, Abr, and FI). Findings The results indicated that participants who viewed the ad with the endorsement showed a more positive Aad than those who viewed the ad without it. The participants with a high congruity condition reported a more positive Abr and higher FI than those with low or medium congruity. Originality/value This study extends the application of congruity theory to banner advertisements, thereby aiding our understanding of consumers’ perceptions of advertising.